Bacteriological profiles of skin flora on early cadaver - Chong, Chi Kwan (2022)
Post-mortem microbiology (PMM) has gained significant importance in the forensic department nowadays to determine the actual cause of death of adults and infants, especially for deaths caused by infection. PMM is of utmost importance when the cadaver does not show any apparent signs of infection. An infective that leads to death is usually suspected in sudden death. Therefore, the determination of infective cause can help in further management of pathogenic transmission and is thus able to prevent the occurrence of outbreaks. However, the current challenge in PMM is the difficulty in interpreting culture results, for example, differentiating the true pathogen from the contaminants, especially when there is a mixed growth in the samples. Mixed growth or contamination from skin flora may induce false positive results, leading to uncertainty and failure in identifying true pathogen. Therefore, information on post-mortem skin flora can be helpful in providing references for interpreting microbiological investigations in post-mortem cases. Early cadavers (n=39), which have an estimated post-mortem (ePMI) of less than 24 hours, under sudden unexpected death cases, were included in this study. Two body sites, namely the neck and femoral, of each cadaver were chosen as the sites to obtain skin samples. Blood samples from these two sites were routinely obtained for post-mortem microbiological culture. Cotton swabs were moistened with normal saline and were then rubbed vigorously and rotated to ensure that homogeneity in the skin areas were achieved by each swab. The swabs were then kept in 200μl of phosphate-buffered saline (PBS) for storage and transportation. DNA was extracted from each skin swab and high-throughput 16S rRNA sequencing was performed on the extracted DNA using the Illumina Miseq system to assess bacterial diversity and abundance. The sequence outputs were analysed by using the LotuS pipeline while the α-diversity and β-diversity were analysed by using the Quantitative Insights into Microbial Ecology (QIIME) software. The samples were mostly predominated by phylum Proteobacteria (61.20%), followed by Firmicutes (28.10%), Actinobacteria (10.00%) and Bacteroidetes (0.60%). In addition, the top 10 dominant genera from the samples were Ochrobactrum (24.70%), Staphylococcus (20.60%), other members of Enterobacteriaceae (17.70%), Corynebacterium (6.00%), Enhydrobacter (5.30%), Acinetobacter (4.30%), Klebsiella (3.40%), Pseudomonas (2.70%), Stenotrophomonas (2.10%) and Phycicoccus (2.00%) accordingly. Moreover, there were no statistical difference between the bacterial communities of the neck and femoral sites, except for genus Corynebacterium which showed significant difference in abundance between both body sites. Nevertheless, the results showed significant difference between the abundance of some bacterial genera found on the cadavers with ePMI less than 5 hours (ePMI<5H) and the cadavers with ePMI more than 5 hours (ePMI>5H). The findings of this study provides data on the known skin flora that presents on early cadavers, thus may help in determining the actual cause of death due to pathogenic infections.